PENGUATAN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM MELALUI MEDIA BUKU CERITA ISLAMI DI SEKOLAH DASAR ISLAM DALAM DISIPLIN ILMU - Aryani Nova Rossydah , Anisah Nur Azizah , Putri Amalia; Rahmahtiawati Marfiyannur Rahmandita , Budi Johan (STKIP Subang, 2025)
This study aims to examine the application of learning media in the form of Islamic story books in Islamic Religious Education (PAI) learning in Elementary Schools through a literature study approach. Islamic story books are one of the media that combine Islamic values with an interesting story approach that is easy for students to understand. In the context of PAI learning, fairy tales can be an effective means of conveying moral messages and religious values in a contextual, enjoyable, and memorable way for students. The results of the study show that the use of Islamic story books provides various benefits, including increasing students' understanding of religious material, fostering interest in learning, and forming character and noble morals from an early age. However, there are also several obstacles faced in its implementation, such as limited availability of appropriate books, lack of teacher skills in storytelling, and limited learning time. To overcome these obstacles, support is needed from the school in providing learning resources, teacher training in Islamic storytelling techniques, and integrating fairy tale media into planned learning strategies. With the right approach, Islamic story books can be an alternative effective and enjoyable learning media in improving the quality of religious education at the elementary level.